1893 Or.§Laws 29-30, An Act to Punish the Pointing of Firearms at a Human Being, § 1. - (:unkn) unknown (My University, 1893)
It shall be unlawful for any person over the age of sixteen years, with or without malice, purposely to point or aim any pistol, gun, revolver, or other firearm, within range of said firearm, either loaded or empty, at or toward any other person, except in self-defense. And any person so offending shall be guilty of a misdemeanor and upon conviction shall be fined in any sum not less than ten dollars nor more than five hundred dollars, or be imprisoned in the county jail not less than ten days nor more than six months, or both.
Keywords: BRANDISHING